Predictive value of changes in the serum CA-125 levels in patients undergoing interval debulking surgery after neoadjuvant chemotherapy in advanced epithelial ovarian carcinoma - Batra, Sonia; Arora, Ruchi; Dave, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study is to evaluate the predictive value of serum CA-125 changes in the management of patients undergoing neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) in advanced epithelial ovarian carcinoma (EOC). Methods: A retrospective hospital-based study of patients with advanced epithelial ovarian cancers (stage III and IV) was conducted at Department of Obstetrics and Gynecology in Gujarat Cancer and Research Institute, Ahmedabad, for two years. Total 50 patients were treated with NACT followed by surgical cytoreduction and followed up till August 2010. Response to NACT, optimal cytoreduction rate and overall response rate were analyzed.CA 125 levels before (baseline) and after NACT were analyzed. Results: Out of 50, there were 43 patients (86%) with stage III disease and 7 (14%) with stage IV disease. Maximum 37(74%) patients had CA 125 levels >500 on presentation while none of the patients had baseline CA125 levels in the normal range (<35). Range of baseline CA 125 was 164-5394.All patients were given NACT and after NACT, out of 50 patients, 22(44%) patients had CA 125 values within the normal range (<35) while 23(46%) had values between 35 and 100. Thus, statistically significant difference (Z = 6.154, P<0.0001) was found between CA 125 level before and after NACT. Out of 45 patients with CA 125 <100, 35(77.8%) underwent optimal cytoreduction. Conclusions: Baseline (prechemotherapy) serum CA-125 levels are powerful indicators of the presence and extent of spread of disease while CA-125 level particularly <100U/ml after NACT strongly predicts optimal cytoreduction in advanced epithelial ovarian cancers.